INCLUSION OF THE SEHANANWA DIALECT IN GRADE 10 LEARNERS' SEPEDI ACADEMIC WRITING: AN ANALYSIS OF DIALECTAL INTERFERENCE - Seanego, James; Moyaha, Sello Treasure (Universitas Islam Sumatera Utara (UISU), 2025)
Home Language learners always face multiple challenges in their formal writing activities. One of these is the frequent inclusion of dialects in their academic writing. There seems to be an unresolved argument regarding whether dialects should be included in the academic writing of a standard language or not. This article aims to analyse how Sehananwa-speaking learners include their dialectal orthography in the Sepedi academic writing. This is a qualitative study located within the interpretivism paradigm. Essays from 4 learners were purposefully sampled using a document review as a data collection method. Thematic steps were incorporated to analyse the collected data. Findings demonstrate that spoken variety plays a great role in differentiating Sehananwa as a dialect and Sepedi as a standard language. Speech sounds and lexicons reflect some gap between Sehananwa and Sepedi, notwithstanding the fact that both languages are sociolinguistically bound. It is also noted that Bahananwa-speaking learners are rigid in maintaining and sustaining the linguistic features of their dialect. The question remains: how is a language deemed officially standard while its dialectal orthographies are not recognised in formal discourses? For language development, vocabulary enhancement and learner academic performance, this study recommends that the incorporation of dialects such as Sehananwa should be allowed in formal settings like educational spaces.